A lightweight PET fiber flame-retardant and environmentally friendly flooring and its preparation method
By matching and hot-pressing the porous skeleton of PET fiber with a phosphorus-containing low-melting-point copolyester bonding phase, the problem of PET flame-retardant fiber materials being difficult to balance in terms of lightweight structure and flame-retardant performance, as well as processing fluidity and heat resistance, has been solved. Stable interlayer bonding and thermal dimensional stability have been achieved, making it suitable for continuous manufacturing and green recycling.
Patent Information
- Application Number
- CN202611282776.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-11-06
AI Technical Summary
Existing PET flame-retardant fiber materials face challenges in balancing low-density structure with flame-retardant properties, processing fluidity, and heat resistance. Traditional methods tend to lead to densification of the fiber core layer, weakening the advantages of lightweight structure.
By matching the ratio of porous PET fiber skeleton to phosphorus-containing low-melting-point copolyester binder and hot pressing, a controlled connection is formed, which improves the flame retardant contribution of phosphorus-containing structure, and maintains the thermal dimensional stability of the finished product through interlayer hot-melt bonding and cooling shaping.
It provides effective flame retardant properties, improves the bonding stability and thermal dimensional stability of the fiber core layer without increasing the density filler ratio, while maintaining a lightweight structure suitable for continuous manufacturing and green recycling.
Smart Images

Figure CN123044079A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyester composite flame-retardant flooring materials, specifically to a lightweight PET fiber flame-retardant and environmentally friendly flooring and its preparation method. Background Technology
[0002] Flooring materials used in building interiors, public transportation, exhibition spaces, and lightweight prefabricated applications typically need to strike a balance between load-bearing capacity, installation, transportation, flame retardancy, dimensional stability, and environmental friendliness. Traditional flooring materials that rely on high filler content or dense solid layers for structural stability often increase the mass per unit area, hindering rapid installation, handling, and subsequent recycling. Using fiber felt or porous core layers to achieve lightweighting requires ensuring interlayer bonding, thermal stability, flame retardancy, and dimensional retention over long-term use. PET materials, with their recyclability, processing adaptability, and fiber web advantages, are suitable as the main system for lightweight flooring materials. However, flooring products still need to withstand flame exposure, heat radiation, foot traffic loads, and temperature and humidity variations in actual use. Therefore, material design cannot solely emphasize flame retardancy; it should also consider core density, fiber connectivity, interlayer bonding strength, and thermal dimensional stability to form a comprehensive structural system suitable for continuous manufacturing and green recycling.
[0003] Existing flame-retardant PET fibers or polyester flame-retardant materials mostly improve combustion safety through the addition of flame retardants, flame-retardant masterbatches, surface finishing, or copolymerization modification. However, added flame retardants in polyester systems can easily lead to problems in terms of dispersion uniformity, migration and precipitation, processing stability, and mechanical retention. While surface finishing can improve the flame retardancy of the fiber surface, it is difficult to form a stable and consistent bonding network in the thickness direction of the porous core layer. Simply increasing the amount of low-melting-point binder can improve hot pressing and interlayer bonding, but it may also make the fiber core layer more compact, weakening the advantages of lightweight structure. For example, Chinese patent CN105463610A discloses a flame-retardant polyester fiber and its preparation method, involving a phosphorus-containing flame-retardant polyester fiber scheme. However, its focus is mainly on flame-retardant modification of the fiber body, and its comprehensive support for low-density fiber core layer, surface backing lamination, hot-melt bridging structure, and continuous hot pressing in flooring materials is still insufficient. Summary of the Invention
[0004] The purpose of this invention is to provide a lightweight PET fiber flame-retardant flooring and its preparation method, solving the current technical problem of difficulty in simultaneously achieving low-density structure and flame-retardant performance, as well as processing fluidity and heat resistance.
[0005] This invention achieves controlled connectivity of the low-melting-point phase on the fiber surface and at fiber intersections by matching the ratio of the porous PET fiber skeleton to the phosphorus-containing low-melting-point copolyester binder phase and hot-pressing. This maintains the lightweight space of the core layer while increasing the effective contribution of the phosphorus-containing structure. Furthermore, the thermo-dimensional stability of the finished product is maintained through interlayer hot-melt bonding and cooling shaping.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A lightweight PET fiber flame-retardant flooring, wherein the PET is polyethylene terephthalate; the lightweight PET fiber flame-retardant flooring comprises a PET surface layer, a PET fiber flame-retardant core layer, and a PET backing layer; Both the PET surface layer and the PET backing layer contain PET; The PET fiber flame-retardant core layer includes a PET fiber-phosphorus-containing low-melting-point copolyester coating, wherein the PET fiber-phosphorus-containing low-melting-point copolyester coating includes PET fibers and a phosphorus-containing low-melting-point copolyester binder phase coating the surface of the PET fibers and at the fiber intersections; The phosphorus-containing low-melting-point copolyester binder phase is obtained by transesterification and polycondensation of dimethyl terephthalate, ethylene glycol, 1,4-cyclohexanediethanol and 2-carboxyethylphenylphosphonic acid in the presence of tetrabutyl titanate.
[0007] Furthermore, the PET fiber-phosphorus-containing low-melting-point copolyester coating is prepared through the following steps: A1. Providing a PET fiber felt, the PET fiber felt comprising PET fibers; A2. Provides a phosphorus-containing low-melting-point copolyester binder phase; A3. The PET fiber felt is compounded with the phosphorus-containing low-melting-point copolyester binder phase, such that the phosphorus-containing low-melting-point copolyester binder phase is distributed on the surface of the PET fiber and at the fiber intersections; A4. The composite material is preheated, hot-pressed, and cooled to set its shape; A5. After thickness determination and edge trimming, the PET fiber-phosphorus-containing low-melting-point copolyester coating is obtained; The moisture content of the PET fiber-phosphorus-containing low-melting-point copolyester coating is 0.02–0.30 wt%.
[0008] Furthermore, the phosphorus-containing low-melting-point copolyester binder phase is prepared through the following steps: B1. Raw material preparation: Based on 100 moles of dimethyl terephthalate, add 115–180 moles of ethylene glycol, 5–35 moles of 1,4-cyclohexanediol, 2–12 moles of 2-carboxyethylphenylphosphonic acid, and tetrabutyl titanate, wherein the amount of tetrabutyl titanate is 0.01–0.08 wt% of the total mass of dimethyl terephthalate, ethylene glycol, 1,4-cyclohexanediol, and 2-carboxyethylphenylphosphonic acid; B2. Transesterification reaction: The transesterification reaction is carried out under an inert atmosphere, and the methanol distillate is collected; B3. Polycondensation reaction: Polycondensation reaction is carried out under reduced pressure to obtain a molten phosphorus-containing low-melting-point copolyester; B4. Post-processing: The molten phosphorus-containing low-melting-point copolyester is extruded, cooled, pelletized, and dried to obtain the phosphorus-containing low-melting-point copolyester binder phase; The intrinsic viscosity of the phosphorus-containing low-melting-point copolyester binder phase is 0.45–0.80 dL / g, and the water content is 0.01–0.08 wt%.
[0009] Furthermore, based on a mass of 100wt% for the PET fiber flame-retardant core layer, the content of the PET fiber is 55–78wt%, the content of the phosphorus-containing low-melting-point copolyester binder phase is 18–40wt%, and the sum of the contents of the PET fiber and the phosphorus-containing low-melting-point copolyester binder phase is 93–100wt%, with the remainder being a PET transition phase located in the interface region of the PET fiber flame-retardant core layer; the phosphorus-containing low-melting-point copolyester binder phase forms a coating structure on the surface of the PET fiber and forms molten bridges at the fiber intersections.
[0010] Furthermore, the PET transition phase is the PET phase located in the interface region adjacent to the PET fiber flame-retardant core layer and the PET surface layer and / or the PET backing layer, and is measured according to the final mass of the PET fiber flame-retardant core layer in the finished product.
[0011] Furthermore, the thickness of the PET fiber flame-retardant core layer is 1.5–6.0 mm, and the apparent density is 0.55–0.95 g / cm³. 3 Furthermore, the recycled PET fibers in the flame-retardant core layer of the PET fiber account for 30–100 wt% of all PET fibers.
[0012] Furthermore, the oxygen index of the lightweight PET fiber flame-retardant flooring is 28–38 vol%, and the critical radiative flux of the lightweight PET fiber flame-retardant flooring is 4.5–15.0 kW / m². 2 .
[0013] Furthermore, the thickness of the PET surface layer is 0.05–0.50 mm, the thickness of the PET backing layer is 0.05–0.80 mm, and the PET surface layer, the PET fiber flame-retardant core layer, and the PET backing layer are bonded together by the hot melt flow of the phosphorus-containing low-melting-point copolyester binder phase.
[0014] Furthermore, the coefficient of variation of the mass applied per unit area of the phosphorus-containing low-melting-point copolyester binder phase on the PET fiber felt is 5–18%, and the coefficient of variation of the thickness of the PET fiber flame-retardant core layer is 2–8%.
[0015] Furthermore, the melting peak temperature of the phosphorus-containing low-melting-point copolyester binder phase is 110–170°C; the phosphorus element in the PET fiber flame-retardant core layer is provided by the phosphorus-containing low-melting-point copolyester binder phase; no chlorine-based or bromine-based flame retardants are added to the PET fiber flame-retardant core layer; and the lightweight PET fiber flame-retardant floor does not include a polyvinyl chloride resin layer.
[0016] As a concept of this invention, the present invention employs a design of PET fiber-phosphorus-containing low-melting-point copolyester coating in a PET fiber flame-retardant core layer, primarily aimed at achieving a synergistic balance between lightweight porous structure and flame-retardant bonding performance. In existing technologies, to reduce the unit area mass of flooring, the porosity of the fiber core layer is typically increased while the amount of binder phase is reduced. However, this approach weakens the effective proportion of the phosphorus-containing structure and the connection at fiber cross-points. To improve flame retardancy and bonding strength, the binder phase or flame-retardant components are often increased, causing core layer densification and compromising lightweight properties. This invention, through the proportional matching of the PET fiber skeleton, phosphorus-containing low-melting-point copolyester binder phase, coating structure, and melt bridges, concentrates the phosphorus-containing binder phase on the fiber surface and cross-points, improving bonding and flame-retardant contribution with limited dosage, and mitigating the side effects of densification, thereby balancing the requirements of low-density structure, interlayer bonding, and combustion safety.
[0017] This invention also discloses a method for preparing lightweight PET fiber flame-retardant flooring, the method comprising the following steps: S1. Provides a PET surface layer, a PET backing layer, and a pre-made PET fiber-phosphorus-containing low-melting-point copolyester coating; S2. The PET surface layer, the PET fiber-phosphorus-containing low-melting-point copolyester coating and the PET backing layer are stacked sequentially to obtain a laminate; S3. The laminate is hot-pressed and cooled to obtain the lightweight PET fiber flame-retardant flooring.
[0018] Further, in step S1, when preparing the PET fiber-phosphorus-containing low-melting-point copolyester coating, the PET fibers are opened, mixed with cotton, combed, laid into a web, and needle-punched to obtain PET fiber felt; the phosphorus-containing low-melting-point copolyester binder phase is applied in the form of powder or low-melting-point short fibers before hot pressing, and the coefficient of variation of the phosphorus-containing low-melting-point copolyester binder phase in the PET fiber felt is 5–18% per unit area.
[0019] Furthermore, the cooling and shaping in step S3 includes cooling the laminate under pressure; the preparation of the PET fiber-phosphorus-containing low-melting-point copolyester coating and steps S2 and S3 are carried out in a continuous manner; the total thickness of the obtained lightweight PET fiber flame-retardant flooring is 2.0–7.3 mm, the interlayer 180° peel strength is 1.0–5.0 N / mm, which is the lower of the average peel strength of the stable peel zone at the interface between the PET surface layer and the PET fiber flame-retardant core layer and the interface between the PET fiber flame-retardant core layer and the PET backing layer, and the thermal dimensional change rate is 0.02–0.30%.
[0020] Furthermore, the PET fibers in the PET fiber felt have a fiber fineness of 2–15 dtex, a fiber length of 38–76 mm, and a fiber moisture content of 0.05–0.50 wt%, with recycled PET fibers accounting for 30–100 wt% of the total PET fibers. The PET fibers are sequentially opened, blended, carded, web-laid, and needle-punched, with opening and blending times of 5–30 min and needle-punching density of 80–300 needles / cm². 2 PET fiber felt is obtained.
[0021] Furthermore, taking 100 moles of dimethyl terephthalate as the basis, 115–180 moles of ethylene glycol, 5–35 moles of 1,4-cyclohexanediol, 2–12 moles of 2-carboxyethylphenylphosphonic acid, and tetrabutyl titanate are added to the reaction system. The amount of tetrabutyl titanate is 0.01–0.08 w of the total mass of dimethyl terephthalate, ethylene glycol, 1,4-cyclohexanediol, and 2-carboxyethylphenylphosphonic acid. t% , under nitrogen protection, an ester exchange reaction was carried out at 160–205℃ for 1.0–4.0 h and the methanol distillate was collected. Subsequently, a polycondensation reaction was carried out at 230–270℃ and 20–200 Pa for 1.0–5.0 h to obtain a molten phosphorus-containing low-melting-point copolyester. The molten phosphorus-containing low-melting-point copolyester was extruded, cooled, pelletized, and dried at 80–120℃ for 4–12 h to obtain a phosphorus-containing low-melting-point copolyester binder phase.
[0022] Furthermore, when the phosphorus-containing low-melting-point copolyester binder phase is applied in powder form, the phosphorus-containing low-melting-point copolyester binder phase is pulverized and sieved into powder with a D50 of 20–150 μm, where D50 is the particle size corresponding to a cumulative volume fraction of 50% as measured by a laser particle size analyzer. When the phosphorus-containing low-melting-point copolyester binder phase is applied in the form of low-melting-point short fibers, the phosphorus-containing low-melting-point copolyester binder phase is spun in a molten state above its melting peak temperature, and then cooled, drawn, crimped, and cut to obtain the low-melting-point short fibers, where the fiber fineness is 2–10 dtex and the length is 20–76 mm. The powder or the low-melting-point short fibers are applied to PET fiber mat, and the phosphorus-containing low-melting-point copolyester binder phase is distributed on the surface, pore walls, and fiber intersections of the PET fibers through spreading, blending, or lamination to obtain composite fiber mat.
[0023] Furthermore, based on the final PET fiber flame-retardant core layer with a mass of 100wt%, the PET fiber is controlled at 55–78wt%, the phosphorus-containing low-melting-point copolyester binder phase is controlled at 18–40wt%, and the sum of the contents of the PET fiber and the phosphorus-containing low-melting-point copolyester binder phase is 93–100wt%, with the remainder being the PET transition phase; the PET fiber felt and the phosphorus-containing low-melting-point copolyester binder phase are metered according to the aforementioned content relationship, and the metered material is sent to the preheating, hot pressing, and cooling and shaping steps.
[0024] Furthermore, in the spreading or blending step, the PET fiber felt is divided into nine equal application areas along both the length and width directions. The applied mass and area of the phosphorus-containing low-melting-point copolyester binder phase in each application area are recorded. The standard deviation of the applied mass per unit area of each application area is divided by the average value of the applied mass per unit area, and then multiplied by 100% to calculate the coefficient of variation of the applied mass per unit area. The coefficient of variation of the applied mass per unit area is 5–18%, resulting in a composite fiber felt with controlled mass distribution.
[0025] Furthermore, the composite fiber felt is preheated at 110–145℃ for 0.5–3.0 min, then hot-pressed at 170–210℃ and 0.60–2.80 MPa for 60–360 s, and then cooled to 50–90℃ at 0.20–1.50 MPa, so that the phosphorus-containing low-melting-point copolyester binder phase forms a coating structure on the surface of PET fibers and forms a melt bridge at the fiber intersection, thus obtaining a PET fiber-phosphorus-containing low-melting-point copolyester coating.
[0026] Furthermore, rectangular samples were cut from the cooled and shaped PET fiber flame-retardant core layer. The sample mass m in grams was measured using a balance, and the sample length l, width w, and thickness t in centimeters were measured. The apparent density was calculated according to ρ=m / (l×w×t), and the apparent density was 0.55–0.95 g / cm³.3 Apparent density is used for quality control of PET fiber flame-retardant core layers.
[0027] Furthermore, the thickness of the PET fiber flame-retardant core layer after cooling and shaping is measured at nine intersection points formed by dividing the length and width directions into three equal parts. The thickness variation coefficient is calculated by dividing the standard deviation of the nine thickness measurements by the average value and multiplying by 100%. The thickness variation coefficient is 2–8%. The thickness variation coefficient and the average thickness are used for the roller gap control in the thickness setting step.
[0028] Furthermore, cross-sectional samples including the thickness direction were cut from the PET fiber-phosphorus-containing low-melting-point copolyester coating, dried and conductive, and then imaged using a scanning electron microscope. The coating rate was calculated as the percentage of the PET fiber surface length covered by the phosphorus-containing low-melting-point copolyester binder phase in the observation area to the total PET fiber surface length in the observation area. The melt bridge ratio was calculated as the percentage of the number of fiber cross-points forming continuous binder phases connecting adjacent PET fibers to the total number of fiber cross-points in the observation area. The coating rate was 55–90%, and the melt bridge ratio was 45–85%. The coating rate and melt bridge ratio were used for structural quality control of the PET fiber-phosphorus-containing low-melting-point copolyester coating.
[0029] Furthermore, a PET surface layer, a PET fiber-phosphorus-containing low-melting-point copolyester coating, and a PET backing layer are sequentially stacked to form a laminate. The laminate is hot-pressed at 170–210°C and 0.60–2.80 MPa for 60–360 s, then cooled to 50–90°C at 0.20–1.50 MPa, and cured at 20–40°C for 4–24 h. This allows the phosphorus-containing low-melting-point copolyester binder phase to form an interlayer bond between the PET surface layer, the PET fiber flame-retardant core layer, and the PET backing layer, and a PET transition phase to form at the interface region of the PET fiber flame-retardant core layer, resulting in a lightweight PET fiber flame-retardant floor with a total thickness of 2.0–7.3 mm.
[0030] Furthermore, by employing continuous nonwoven web laying equipment, continuous binder phase application equipment, and continuous hot press roller pressing equipment, the PET fiber felt formation, phosphorus-containing low-melting-point copolyester binder phase application, PET fiber-phosphorus-containing low-melting-point copolyester coating preparation, lamination, hot pressing, and cooling shaping are carried out sequentially and continuously to obtain continuously produced lightweight PET fiber flame-retardant flooring.
[0031] Furthermore, the complete flooring, comprising a PET surface layer, a PET fiber flame-retardant core layer, and a PET backing layer, after curing, was used as a sample. The oxygen index was determined according to the sample size, conditioning conditions, and test procedures specified in GB / T 2406.2-2009, and the critical radiative flux was determined according to the sample size, conditioning conditions, and test procedures specified in GB / T11785-2005. The oxygen index and critical radiative flux data were recorded; the oxygen index was 28–38 vol%, and the critical radiative flux was 4.5–15.0 kW / m². 2 The oxygen index and critical radiation flux are then used for finished product quality control.
[0032] As another aspect of this invention, the present invention employs a process of sequentially stacking a PET surface layer, a PET fiber-phosphorus-containing low-melting-point copolyester coating, and a PET backing layer, followed by hot pressing and cooling for shaping. This method is primarily used to achieve the aforementioned synergistic effect. Existing methods, while enhancing interlayer bonding by simply increasing the hot pressing temperature or pressure, may compact the fiber core layer and weaken the lightweight structure. Conversely, reducing processing intensity to maintain porosity makes it difficult to form stable interlayer bonding and fiber cross-point connections. This invention, by first forming a phosphorus-containing low-melting-point copolyester coating and then performing lamination hot pressing and pressurized cooling, allows the binder phase to flow in a controlled manner within the fiber network and the interface between the surface and backing layers. This enables the formation of a coating structure and melt bridges under process conditions while maintaining controllable core layer thickness and density, thereby achieving a balance between flame retardancy, processability, interlayer bonding, and thermal dimensional stability.
[0033] Beneficial technical effects 1. Balancing lightweight structure and flame retardant safety: By forming a porous skeleton through PET fiber felt and distributing the phosphorus-containing low-melting-point copolyester binder phase on the surface of PET fibers and fiber intersections, phosphorus-containing flame retardant contribution can be provided without relying on a high proportion of dense filling, thus improving the problem of insufficient flame retardant support in traditional lightweight fiber core layers.
[0034] 2. Improve the stability of fiber core layer connection: The phosphorus-containing low-melting-point copolyester binder undergoes controlled thermal melt flow during hot pressing, forming a coating structure on the surface of PET fibers and forming melt bridges at fiber intersections, transforming the dispersed fiber network into a stable connection structure, thereby improving the problems of weak interlayer bonding and insufficient dimensional retention of simple needle-punched fiber felt.
[0035] 3. Improve the balance between processing fluidity and heat resistance: By forming a phosphorus-containing low-melting-point copolyester binder phase with dimethyl terephthalate, ethylene glycol, 1,4-cyclohexanediethanol and 2-carboxyethylphenylphosphonic acid, we can impart wetting and flowability during hot pressing, and maintain the predetermined thermal dimensional change rate of the finished product through cooling and shaping.
[0036] 4. Enhance greening and recycling adaptability: The PET surface layer, PET fiber flame-retardant core layer and PET backing layer all contain PET materials, and the PET fiber flame-retardant core layer can contain recycled PET fibers, while not including the polyvinyl chloride resin layer, which helps to reduce the difficulty of separating multiple materials and improve the environmental adaptability of the flooring material.
[0037] 5. Suitable for continuous manufacturing and quality control: Through continuous processes such as opening, blending, carding, web laying, needle punching, application of binder phase, preheating, hot pressing and cooling, process control can be achieved by combining the coefficient of variation of applied mass per unit area, thickness coefficient of variation, coverage rate and melt bridge ratio, which is beneficial for quality control in continuous manufacturing processes. Attached Figure Description
[0038] Figure 1 This is a graph showing the effect of preheating temperature on fiber surface coverage and melt bridge ratio in Example 1.
[0039] Figure 2 This is a quantitative comparison chart of the SEM coverage of the cross sections of Example 1, Comparative Example 10, and Comparative Example 11.
[0040] Figure 3 This is a comparison diagram of the 180° peel strength between layers in Example 1, Comparative Example 4, and Comparative Example 10.
[0041] Figure 4 The DSC heat flow curves are for the phosphorus-containing low-melting-point copolyester binder phase of Example 1 and the low-melting-point copolyester binder phase of Comparative Example 9.
[0042] Figure 5 This is a diagram showing the actual process parameters for the continuous hot pressing roller pressing process.
[0043] Figure 6 The images show a comparison of the SEM morphology and SEM-EDS surface scans of the final product of Example 1 and the final product of Comparative Example 10; wherein, Figure 6 Figure a in the image is a medium-magnification SEM image of the core fiber interwoven network and fused bridge structure of the final product of Example 1; Figure 6 Figure b in the figure is a medium-magnification SEM image of the distribution of the bonding phase at the fiber cross-points of the core layer of the final product in Comparative Example 10. Figure 6 Figure c in the image is a high-magnification SEM image of the fiber surface coating, melt bridges, and pore edges of the final product of Example 1. Figure 6 Figure d in the figure is a high-magnification SEM image of the plate-like binder phase enrichment area and the insufficient bridging area inside the core layer of the final product of Comparative Example 10. Figure 6 Figure e in the figure is a SEM-EDS surface scan of the spatial distribution of the P element in the final product of Example 1; Figure 6 Figure f in the diagram is a SEM-EDS surface scan of the spatial distribution of P element in the final product of Comparative Example 10. Detailed Implementation
[0044] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0045] Example 1
[0046] In this embodiment, a batch of lightweight PET fiber flame-retardant flooring samples with a total feed weight of 5.0 kg was prepared. The product form was a sheet material consisting of a PET surface layer, a PET fiber flame-retardant core layer, and a PET backing layer layer laminated sequentially. The PET surface layer used commercially available PET sheets with a thickness of 0.25 mm; the PET backing layer used commercially available PET sheets with a thickness of 0.25 mm; the PET fiber flame-retardant core layer was mainly composed of PET fiber-phosphorus-containing low-melting-point copolyester coating, with a core layer thickness of 1.5 mm and an apparent density of 0.56 g / cm³. 3 The total thickness is 2.0mm.
[0047] Step 1: Preparation of PET fiber felt Commercially available PET fibers with a fineness of 2 dtex, a length of 38 mm, and a moisture content of 0.05 wt% were selected, of which recycled PET fibers accounted for 30 wt% of the total PET fibers. The PET fibers were opened and blended with cotton for 5 minutes, then carded, web-laid, and needle-punched to form a PET fiber felt with a needle-punching density of 80 needles / cm². 2 .
[0048] Step 2: Preparation of phosphorus-containing low-melting-point copolyester binder phase With dimethyl terephthalate as 100 moles, 115 moles of ethylene glycol, 5 moles of 1,4-cyclohexanediethanol, 2 moles of 2-carboxyethylphenylphosphonic acid, and tetrabutyl titanate were added to a reactor. The amount of tetrabutyl titanate accounted for 0.01 wt% of the total mass of the four reactants. Under nitrogen protection, the temperature was raised to 160°C for a transesterification reaction for 1.0 h, and the methanol distillate was collected. Subsequently, the system was heated to 230°C and subjected to a polycondensation reaction at 20 Pa for 1.0 h to obtain a molten phosphorus-containing low-melting-point copolyester. The molten phosphorus-containing low-melting-point copolyester was extruded, cooled, pelletized, and dried at 80°C for 4 h to obtain a phosphorus-containing low-melting-point copolyester binder phase. The intrinsic viscosity of the phosphorus-containing low-melting-point copolyester binder phase in this embodiment was 0.45 dL / g, and the water content was 0.01 wt%.
[0049] Step 3: Constructing a PET fiber-phosphorus-containing low-melting-point copolyester coating The phosphorus-containing low-melting-point copolyester binder phase was pulverized and sieved into powder with a D50 of 20 μm. Based on a final PET fiber flame-retardant core layer mass of 100 wt%, the PET fiber content was controlled at 55 wt%, and the phosphorus-containing low-melting-point copolyester binder phase at 40 wt%. The PET fiber felt was divided into nine equal application areas along both its length and width directions. Powder was spread according to the area of each area, with a coefficient of variation of 5% for the applied mass per unit area. The spread composite fiber felt was preheated at 110℃ for 0.5 min, hot-pressed at 170℃ and 0.60 MPa for 60 s, and then cooled to 50℃ at 0.20 MPa. After thickness determination and edge trimming, a PET fiber-phosphorus-containing low-melting-point copolyester coating with a moisture content of 0.02 wt% was obtained.
[0050] Step 4: Layered Formulation A PET surface layer, a PET fiber-phosphorus-containing low-melting-point copolyester overlay, and a PET backing layer are sequentially stacked to form a laminate. The laminate is then hot-pressed at 170℃ and 0.60MPa for 60s, cooled to 50℃ at 0.20MPa, and cured at 20℃ for 4 hours. During the lamination process, the phosphorus-containing low-melting-point copolyester binder phase forms an interlayer bond between the PET surface layer, the PET fiber flame-retardant core layer, and the PET backing layer.
[0051] Quality testing methods and results Rectangular samples were cut and tested for apparent density, thickness variation coefficient, coverage, melt bridge ratio, oxygen index of intact floor, critical radiative flux, 180° peel strength between layers, and thermal dimensional change rate of PET fiber flame retardant core layer. The relevant test results were recorded according to the measured statistical values in Table 1.
[0052] Features and application scenarios of this embodiment This embodiment uses a lower PET fiber content and mild hot-pressing conditions, resulting in a lower core density and lighter overall material weight. It is suitable for use in indoor temporary paving, exhibition spaces, and lightly loaded areas where there are requirements for paving weight, portability, and basic flame retardancy.
[0053] Example 2
[0054] The raw materials and proportions were determined according to a total input scale of 8.0 kg for lightweight PET fiber flame-retardant flooring samples. The PET surface layer was commercially available PET sheet with a thickness of 0.50 mm; the PET backing layer was commercially available PET sheet with a thickness of 0.80 mm; and the PET fiber flame-retardant core layer had a thickness of 6.0 mm and an apparent density of 0.94 g / cm³. 3 The total thickness is controlled at 7.3 mm. Based on the mass of 100 wt% of the PET fiber flame-retardant core layer, the PET fiber content is 78 wt%, the phosphorus-containing low-melting-point copolyester binder content is 18 wt%, and the balance is PET transition phase.
[0055] The PET fiber felt preparation process uses commercially available PET fibers with a fineness of 15 dtex, a length of 76 mm, and a moisture content of 0.50 wt%, of which recycled PET fibers account for 100 wt% of the total PET fibers. After opening and blending with cotton for 30 minutes, the PET fibers are carded, web-laid, and needle-punched to form PET fiber felt with a needle-punching density of 300 needles / cm². 2 .
[0056] The preparation process of the phosphorus-containing low-melting-point copolyester binder phase involves adding 180 moles of ethylene glycol, 35 moles of 1,4-cyclohexanediol, 12 moles of 2-carboxyethylphenylphosphonic acid, and tetrabutyl titanate to the reaction system, with tetrabutyl titanate accounting for 0.08 wt% of the total mass of the four reactants, based on a dimethyl terephthalate motif of 100 moles. A transesterification reaction was carried out at 205 °C for 4.0 h under nitrogen protection, and the methanol distillate was collected. Subsequently, a polycondensation reaction was carried out at 270 °C and 200 Pa for 5.0 h to obtain a molten phosphorus-containing low-melting-point copolyester. The molten phosphorus-containing low-melting-point copolyester was extruded, cooled, pelletized, and dried at 120 °C for 12 h to obtain the phosphorus-containing low-melting-point copolyester binder phase. The intrinsic viscosity of the phosphorus-containing low-melting-point copolyester binder phase was 0.80 dL / g, and the water content was 0.08 wt%.
[0057] In the compounding and shaping process, the phosphorus-containing low-melting-point copolyester binder phase was pulverized and sieved into powder with a D50 of 150 μm, and then applied to PET fiber mat by spreading. The mass applied per unit area of the PET fiber mat was recorded for nine application areas, with a coefficient of variation of 18%. The composite fiber mat was preheated at 145℃ for 3.0 min, hot-pressed at 210℃ and 2.80 MPa for 360 s, and then cooled to 90℃ at 1.50 MPa. After thickness determination and edge trimming, a PET fiber-phosphorus-containing low-melting-point copolyester coating with a moisture content of 0.30 wt% was obtained.
[0058] In the lamination and post-processing process, the PET surface layer, the PET fiber-phosphorus-containing low-melting-point copolyester overlay, and the PET backing layer are sequentially stacked to obtain the laminate. The laminate is hot-pressed at 210℃ and 2.80MPa for 360s, then cooled to 90℃ at 1.50MPa, and cured at 40℃ for 24h to obtain lightweight PET fiber flame-retardant flooring.
[0059] Quality testing methods and results: The apparent density of the PET fiber flame-retardant core layer, thickness variation coefficient, coverage rate, melt bridge ratio, oxygen index of the intact floor, critical radiation flux, 180° peel strength between layers, and thermal dimensional change rate of the obtained lightweight PET fiber flame-retardant floor were tested. The relevant test results are recorded according to the measured statistical values in Table 1.
[0060] Features of the solution in this embodiment This embodiment uses a high PET fiber content and strong hot-pressing conditions, making it suitable for indoor paving scenarios with high requirements for flame retardant performance and interlayer bonding.
[0061] Example 3
[0062] This embodiment uses a medium-ratio, short-fiber blending method to prepare lightweight PET fiber flame-retardant flooring. The production scale is 6.0 kg. The PET surface layer uses commercially available PET sheets with a thickness of 0.05 mm, the PET backing layer uses commercially available PET sheets with a thickness of 0.05 mm, the PET fiber flame-retardant core layer has a thickness of 3.5 mm, and the total thickness of the finished product is 3.6 mm. In the PET fiber flame-retardant core layer, the PET fiber content is 65 wt%, the phosphorus-containing low-melting-point copolyester binder phase content is 28 wt%, and the balance is a PET transition phase.
[0063] The preparation process begins with the fabrication of PET fiber mat. The PET fibers used have a fineness of 8 dtex, a length of 51 mm, and a moisture content of 0.20 wt%, with recycled PET fibers comprising 60 wt% of the total PET fiber composition. After opening and blending with cotton for 18 minutes, the PET fibers are carded, laid into a web, and needle-punched. The needle-punching density of the PET fiber mat is 180 needles / cm². 2 .
[0064] Subsequently, a phosphorus-containing low-melting-point copolyester binder phase was prepared. Based on a dimethyl terephthalate molar ratio of 100, 145 mol parts of ethylene glycol, 20 mol parts of 1,4-cyclohexanediethanol, 7 mol parts of 2-carboxyethylphenylphosphonic acid, and tetrabutyl titanate were added to the reaction system, with tetrabutyl titanate accounting for 0.04 wt% of the total mass of the four reactants. The transesterification reaction was carried out at 185 °C for 2.5 h under nitrogen protection, and the methanol distillate was collected. Subsequently, a polycondensation reaction was carried out at 250 °C and 80 Pa for 3.0 h. The resulting molten phosphorus-containing low-melting-point copolyester was extruded, cooled, pelletized, and dried at 100 °C for 8 h. The intrinsic viscosity of the obtained phosphorus-containing low-melting-point copolyester binder phase was 0.62 dL / g, and the water content was 0.04 wt%.
[0065] In this embodiment, a phosphorus-containing low-melting-point copolyester binder phase is melt-spun, cooled, drawn, crimped, and cut to form low-melting-point short fibers for application. The low-melting-point short fibers have a fineness of 2 dtex and a length of 20 mm. The low-melting-point short fibers are blended and laminated with PET fiber mat to form a composite fiber mat, and the coefficient of variation of the applied mass per unit area of the composite fiber mat is 10%. The composite fiber mat is preheated at 130°C for 1.5 min, hot-pressed at 190°C and 1.50 MPa for 180 s, and then cooled to 70°C at 0.80 MPa. After thickness determination and edge trimming, a PET fiber-phosphorus-containing low-melting-point copolyester coating with a moisture content of 0.12 wt% is obtained.
[0066] During lamination, the PET surface layer, PET fiber-phosphorus-containing low-melting-point copolyester coating, and PET backing layer are sequentially stacked, hot-pressed at 190℃ and 1.50MPa for 180s, cooled to 70℃ at 0.80MPa, and cured at 30℃ for 12h. This process can be implemented on a continuous production line.
[0067] Quality testing methods and results The obtained lightweight PET fiber flame-retardant flooring was tested for apparent density of PET fiber flame-retardant core layer, coefficient of variation of thickness, coverage rate, melt bridge ratio, oxygen index of intact flooring, critical radiative flux, 180° peel strength between layers and thermal dimensional change rate. The relevant test results were recorded according to the measured statistical values in Table 1.
[0068] Applicable scenarios of this embodiment This embodiment uses a medium ratio, short fiber blending, and medium hot pressing process, which is suitable for ordinary indoor paving scenarios.
[0069] Example 4
[0070] I. Preparation Object and Layered Structure: Using 7.0 kg lightweight PET fiber flame-retardant flooring as the preparation object, the product includes a PET surface layer, a PET fiber flame-retardant core layer, and a PET backing layer. The PET surface layer thickness is 0.40 mm, the PET backing layer thickness is 0.60 mm, the PET fiber flame-retardant core layer thickness is 4.5 mm, the total thickness of the finished product is 5.5 mm, and the apparent density of the core layer is 0.84 g / cm³. 3 .
[0071] II. Formation of PET Fiber Felt: Commercially available PET fibers with a fineness of 10 dtex, a length of 64 mm, and a moisture content of 0.35 wt% are used, of which recycled PET fibers account for 85 wt% of the total PET fibers. The PET fibers are opened and blended with cotton for 25 minutes, then carded, web-laid, and needle-punched to form PET fiber felt with a needle-punching density of 240 needles / cm². 2 .
[0072] III. Preparation of Phosphorus-Containing Low-Melting-Point Copolyester Binder Phase: Based on 100 moles of dimethyl terephthalate, 160 moles of ethylene glycol, 30 moles of 1,4-cyclohexanediethanol, 10 moles of 2-carboxyethylphenylphosphonic acid, and tetrabutyl titanate were added. The amount of tetrabutyl titanate accounted for 0.06 wt% of the total mass of the four reactants. A transesterification reaction was carried out at 195 °C for 3.2 h under nitrogen protection, and the methanol distillate was collected. Subsequently, a polycondensation reaction was carried out at 260 °C and 150 Pa for 4.0 h to obtain a molten phosphorus-containing low-melting-point copolyester. The molten phosphorus-containing low-melting-point copolyester was extruded, cooled, pelletized, and dried at 110 °C for 10 h to obtain a phosphorus-containing low-melting-point copolyester binder phase with an intrinsic viscosity of 0.70 dL / g and a water content of 0.06 wt%.
[0073] IV. Formation of Composite Fiber Felt and Cover: The phosphorus-containing low-melting-point copolyester binder phase is applied in the form of low-melting-point short fibers after melt spinning, cooling, drawing, crimping, and cutting. The fiber fineness of the low-melting-point short fibers is 10 dtex, and the length is 76 mm. Based on a PET fiber flame-retardant core layer mass of 100 wt%, the PET fiber content is 70 wt%, the phosphorus-containing low-melting-point copolyester binder phase content is 30 wt%, and the balance is a PET transition phase. The low-melting-point short fibers are composited with PET fiber felt through blending and lamination, with a coefficient of variation of 14% for the applied mass per unit area. The composite fiber felt is preheated at 140℃ for 2.5 min, hot-pressed at 200℃ and 2.20 MPa for 300 s, and then cooled to 80℃ at 1.20 MPa. After thickness determination and edge trimming, a PET fiber-phosphorus-containing low-melting-point copolyester cover is obtained with a moisture content of 0.20 wt%.
[0074] V. Lamination and Continuous Production: The PET surface layer, PET fiber-phosphorus-containing low-melting-point copolyester coating, and PET backing layer are sequentially stacked to form a laminate. The laminate is hot-pressed at 200℃ and 2.20MPa for 300s, then cooled to 80℃ at 1.20MPa, and cured at 35℃ for 18h. When using continuous nonwoven web laying equipment, continuous binder phase application equipment, and continuous hot pressing roller equipment, the formation of PET fiber mat, application of phosphorus-containing low-melting-point copolyester binder phase, coating preparation, lamination, hot pressing, and cooling and shaping can be carried out sequentially and continuously.
[0075] VI. Quality Testing Methods and Results: The apparent density, thickness variation coefficient, coverage, melt bridge ratio, oxygen index of the intact flooring, critical radiative flux, 180° peel strength between layers, and thermal dimensional change rate of the obtained lightweight PET fiber flame-retardant flooring were tested. The relevant test results were recorded according to the measured statistical values in Table 1.
[0076] The process features and application directions of this embodiment This embodiment employs a high proportion of recycled PET fiber, high hot-pressing strength, and a continuous rolling process, making it suitable for the continuous production of prefabricated building interior flooring materials.
[0077] Comparative Example 1: Basically the same as Example 1, except that the PET fiber content in the PET fiber flame-retardant core layer is adjusted to 50 wt%, the phosphorus-containing low-melting-point copolyester binder phase content is maintained at 40 wt%, and the remainder is the PET transition phase. Except for the above differences, the other raw material composition and process conditions are the same as in Example 1.
[0078] Comparative Example 2: Essentially the same as Example 1, except that the content of the phosphorus-containing low-melting-point copolyester binder phase in the PET fiber flame-retardant core layer was adjusted to 15 wt%, the PET fiber content remained at 55 wt%, and the remainder was the PET transition phase. Apart from the above differences, the remaining raw material composition and process conditions were the same as in Example 1.
[0079] Comparative Example 3: Basically the same as Example 1, except that the apparent density of the PET fiber flame-retardant core layer was adjusted to 1.05 g / cm³ by adjusting the gap between the thickness rollers. 3 Apart from the differences mentioned above, the composition of the raw materials and the process conditions are the same as in Example 1.
[0080] Comparative Example 4: Basically the same as Example 1, except that the hot-pressing temperature of both the composite fiber felt and the laminate was adjusted to 150°C. Apart from the above differences, the remaining raw material composition and process conditions are the same as in Example 1.
[0081] Comparative Example 5: Basically the same as Example 1, except that the hot pressing pressure of both the composite fiber felt and the laminate was adjusted to 3.30 MPa. Apart from the above differences, the remaining raw material composition and process conditions were the same as in Example 1.
[0082] Comparative Example 6: Essentially the same as Example 1, except that the amount of 2-carboxyethylphenylphosphonic acid used in preparing the phosphorus-containing low-melting-point copolyester binder phase was adjusted to 1 mole. Apart from the above differences, the remaining raw material composition and process conditions were the same as in Example 1.
[0083] Comparative Example 7: Basically the same as Example 1, except that the PET surface layer thickness was adjusted to 0.02 mm. Except for the above differences, the other raw material composition and process conditions are the same as in Example 1.
[0084] Comparative Example 8: Basically the same as Example 1, except that the coefficient of variation of the applied mass per unit area of the phosphorus-containing low-melting-point copolyester binder phase in the spreading step was adjusted to 25%. Apart from the above differences, the other raw material composition and process conditions are the same as in Example 1.
[0085] Comparative Example 9: Essentially the same as Example 1, except that the phosphorus-containing low-melting-point copolyester binder phase was replaced with a low-melting-point copolyester binder phase without 2-carboxyethylphenylphosphonic acid structural units. The content of the low-melting-point copolyester binder phase was 40 wt%, and the PET fiber content was 55 wt%. Except for the binder phase composition, the other raw material composition and process conditions were the same as in Example 1. This comparative example was used to examine the synergistic relationship between PET fiber and the phosphorus-containing low-melting-point copolyester binder phase.
[0086] Comparative Example 10: Essentially the same as Example 1, except that the phosphorus-containing low-melting-point copolyester binder phase was not applied as powder to the interior of the PET fiber felt. Instead, a 0.20 mm thick sheet-like interlayer was first formed and placed on the surface of the PET fiber felt. The total content of the phosphorus-containing low-melting-point copolyester binder phase remained at 40 wt%. Except for the method of applying the binder phase, the other raw material composition and process conditions were the same as in Example 1. This comparative example was used to examine the synergistic relationship between the coating structure and the melt bridge at the fiber cross-points.
[0087] Comparative Example 11: Essentially the same as Example 1, except that the preheating step was omitted, and the spread composite fiber felt was directly fed into the hot press. The hot pressing temperature remained 170°C, the hot pressing pressure remained 0.60 MPa, and the hot pressing time remained 60 s. Except for the preheating step, the raw material composition and process conditions were the same as in Example 1. This comparative example was used to examine the synergistic relationship between the preheating, hot pressing, and cooling / setting sequence.
[0088] Characterization and performance testing: The formulation, thickness, apparent density, and process parameters in the main text of the examples are the actual control values of the corresponding batches; the values in Table 1 are the measured average value ± standard deviation of 3 parallel samples of the corresponding batch, where the value after "±" represents the standard deviation.
[0089] When testing the intrinsic viscosity of phosphorus-containing low-melting-point copolyester binder phase, the dried granules or low-melting-point short fiber sample were dissolved in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane at a mass ratio of 60:40 to prepare a polymer solution with a concentration of 0.5 g / dL. The outflow time was measured using an Ubbelohde viscometer under constant temperature conditions of 25°C, and the intrinsic viscosity was obtained by dilution extrapolation method, with the unit being dL / g.
[0090] When testing the moisture content of phosphorus-containing low-melting-point copolyester binder phase and PET fiber-phosphorus-containing low-melting-point copolyester coating, dried samples were taken, and the mass of moisture in the samples was determined by the Karl Fischer method. The moisture content was recorded as a percentage of the mass of moisture to the mass of the sample, in wt%.
[0091] When performing DSC tests on phosphorus-containing low-melting-point copolyester binder phases, 5–10 mg of dry sample was placed in an aluminum crucible and heated from 40 °C to 220 °C at a heating rate of 10 °C / min under a nitrogen atmosphere. The heat flow curve was recorded, and the temperature of the endothermic peak was taken as the melting peak temperature.
[0092] When performing structural and elemental quality control on phosphorus-containing low-melting-point copolyester binder phases, dried granules, powders, or low-melting-point short fibers are taken, and FTIR spectra are recorded. 31P-NMR spectrum and phosphorus mass fraction; phosphorus mass fraction was determined by elemental analysis or ICP-OES, and the above test records were kept in correspondence with the 2-carboxyethylphenylphosphonic acid feeding records of the corresponding batches for batch consistency verification of phosphorus-containing low-melting-point copolyester binder phase.
[0093] The complete floorboards prepared in Examples 1–4 and Comparative Examples 1–11 were cut to specified dimensions and conditioned for humidity. The oxygen index was then tested to evaluate the effect of phosphorus-containing low-melting-point copolyester adhesives on the relative flame retardancy. The principle is to determine the minimum oxygen concentration required to sustain combustion in an oxygen-nitrogen mixture. In this example, the oxygen index was measured according to the test procedure specified in GB / T 2406.2-2009 "Determination of Flammability by Oxygen Index Method for Plastics – Part 2: Room Temperature Test". A higher value indicates better flame retardant performance.
[0094] Using a complete floorboard as a sample of flooring material, the critical radiative flux was tested to evaluate the flame propagation resistance of the laminated surface, core, and backing layers under a radiant heat source. The principle involves recording the location where flame propagation ceases in a controlled radiant heat field and calculating the heat flux. This embodiment uses the test procedure specified in GB / T 11785-2005 "Determination of Combustion Performance of Flooring Materials - Radiant Heat Source Method" to determine the critical radiative flux, with units of kW / m². 2 A higher value indicates better performance.
[0095] The apparent density and thickness uniformity of the PET fiber flame-retardant core layer were tested to evaluate its lightweight structure and thickness control capability. The principle involved calculating density from mass and geometric volume, and then calculating the degree of variation using nine-point thickness measurements. The samples were equilibrated at 23℃ and 50% relative humidity for 24 hours. Mass, length, width, and thickness were measured, and the apparent density was calculated using ρ = m / (l×w×t). Thickness was measured along the intersection of the length and width at three equal points, and the coefficient of variation was calculated. The units for apparent density and thickness coefficient of variation are g / cm³, respectively. 3 and%.
[0096] The purpose of conducting 180° peel strength tests on intact flooring is to evaluate the interlayer bonding formed by the phosphorus-containing low-melting-point copolyester binder phase between the PET surface layer, the PET fiber flame-retardant core layer, and the PET backing layer. The principle is to peel the interlayer interfaces at a constant speed and record the peel force per unit width. The samples were cut into strips 25 mm wide and 200 mm long, equilibrated for 24 hours at 23°C and 50% relative humidity, and then peeled at 180° at a speed of 100 mm / min. The average value of the stable peel area was taken. The average peel strength of the stable peel area of each interface was taken when testing the interface between the PET surface layer and the PET fiber flame-retardant core layer, and the interface between the PET fiber flame-retardant core layer and the PET backing layer. Table 1 records the lower of the average peel strength of the two interfaces. The higher the value, the better the interlayer bonding.
[0097] The purpose of conducting a thermal dimensional change rate test on complete floorboards is to evaluate the dimensional stability of the finished product under heat exposure after the introduction of a low-melting-point binder phase; the principle is to compare the length change before and after heating. Samples are cut into 250mm × 50mm strips and equilibrated for 24 hours at 23℃ and 50% relative humidity. After measuring the initial length, the strips are placed in an 80℃ hot air environment for 6 hours, then cooled to 23℃ and the length is measured again. The thermal dimensional change rate is calculated as the percentage of the absolute value of the length change before and after heating to the initial length; a lower value indicates better dimensional stability.
[0098] Quantitative scanning electron microscopy analysis was performed on the cross-section of PET fiber-phosphorus-containing low-melting-point copolyester coatings to evaluate the structural contribution of the phosphorus-containing low-melting-point copolyester binder phase on the PET fiber surface and at fiber cross-sections. The principle was to statistically analyze the length of the covered fiber surface and the number of cross-sections forming continuous connections using cross-sectional images. Samples were dried, sectioned, and conductively treated before imaging. Five fields of view were selected for each sample, and the coating rate and melt bridge ratio were statistically analyzed. The statistical average of the five fields of view was used as the coating rate and melt bridge ratio of the sample, in percentages (%).
[0099] To verify the improvement effect of the lightweight PET fiber flame-retardant flooring and its preparation method described in this invention on the problems of "difficulty in balancing low-density structure and flame-retardant performance, and difficulty in balancing processing fluidity and heat resistance", the following is combined with Figures 1 to 6 The key process windows, interface structure formation, interlayer bonding performance, thermal behavior characteristics, continuous production process conditions, and spatial distribution of flame-retardant elements are explained. The results shown in each figure are presented in sequence according to the relationship between process conditions, thermal behavior, interface structure, and performance testing, including preheating temperature, cross-sectional coating, interlayer delamination, DSC heat flux, process parameter records of continuous hot pressing and rolling, and spatial distribution of P element signal.
[0100] like Figure 1As shown, based on the formulation system and hot pressing conditions of Example 1, only the preheating temperature was changed, and the comparison was made within the range of 100–155℃. The results show that as the preheating temperature increases, the fiber surface coverage and melt bridge ratio both show a trend of first increasing and then decreasing, reaching an optimal level around 128℃. This result indicates that a higher preheating temperature is not necessarily more beneficial: when the preheating temperature is too low, the phosphorus-containing low-melting-point copolyester binder phase is not sufficiently softened, making it difficult to fully wet the PET fiber surface, and the effective bridging structure at fiber intersections is insufficient; when the preheating temperature is too high, the low-melting-point phase undergoes excessive flow or local migration, easily causing local enrichment, pore blockage, or uneven distribution of the binder phase, thereby reducing the effective coverage of the fiber surface and the cross-point bridging ratio. Therefore, a preheating condition of approximately 128℃ can keep the low-melting-point binder phase in a moderately softened state, maintaining the porous and lightweight space of the core layer while improving its wetting, coverage, and connection efficiency on the fiber surface and fiber intersections, providing a stable interface structure basis for subsequent hot pressing.
[0101] Based on the interface structure formed under the above preheating conditions, further... Figure 2 Quantitative comparisons were made of the cross-sectional SEM coating rates of different samples. Multi-field statistical analysis of the cross-sectional images of Example 1, Comparative Example 10, and Comparative Example 11 showed that the fiber surface coating rate of Example 1 was 55.8%, significantly higher than the 25.2% of Comparative Example 10 and 40.0% of Comparative Example 11. This result indicates that the method of matching the ratio of the porous PET fiber skeleton to the phosphorus-containing low-melting-point copolyester binder phase in this invention enables the binder phase to be more fully distributed on the fiber surface and in the fiber cross-section areas. In contrast, the binder phase coverage in Comparative Example 10 and Comparative Example 11 was insufficient or had poor distribution continuity, making it difficult to form a stable multi-point coating and connection structure within the core layer. Therefore, this invention does not simply rely on increasing the content of the low-melting-point binder phase to improve bonding strength, but rather improves the effective area of interfacial bonding and the participation efficiency of the phosphorus-containing structure by enabling the phosphorus-containing low-melting-point copolyester to form an effective coating layer and connection points within the fiber network, while maintaining a low-density porous structure.
[0102] The contribution of the aforementioned coating structure to the interlayer bonding performance can be derived from... Figure 3Further explanation. Interlaminar 180° peel strength tests were conducted on Examples 1, 4, and 10. The peel strength of Example 1 was 1.05 N / mm, while that of Comparative Examples 4 and 10 were 0.45 N / mm and 0.50 N / mm, respectively. The peel strength of Example 1 was significantly higher than that of the two control samples, indicating that the phosphorus-containing low-melting-point copolyester binder phase in this invention can not only form a coating structure on the surface of the core fiber but also play an effective bonding role during interlaminar thermal fusion bonding. Especially when the low-melting-point binder phase forms molten bridges at fiber intersections, the interlaminar load no longer mainly relies on local point adhesion or sheet-like interlayer adhesion, but is transferred through multi-point bridging structures in the fiber network, thereby improving interlaminar peel resistance. This result demonstrates that the porous fiber skeleton-phosphorus-containing low-melting-point copolyester binder phase composite structure formed by this invention can balance lightweight structure maintenance with improved interlaminar bonding strength.
[0103] Figure 4 The DSC heat flow curves of the phosphorus-containing low-melting-point copolyester binder phase of Example 1 and the low-melting-point copolyester binder phase of Comparative Example 9 are shown to record the melting peak temperature of the corresponding samples.
[0104] Figure 5 The process parameter records for the continuous hot pressing roll forming process are shown, reflecting the process conditions during continuous production.
[0105] Furthermore, Figure 6 The microstructure and spatial distribution of elemental signals of the present invention are observed and explained by SEM morphology and SEM-EDS surface scan results of the final product. Figure 6 Image a is a medium-magnification SEM image of the final product of Example 1, showing that the PET fibers form an interwoven network in the core layer, and that coating and fused bridge structures are visible at the fiber intersections. In contrast, Figure 6 In the final product of Comparative Example 10 shown in b, the distribution of the binder phase at the intersection of PET fibers is insufficient, and there are local bare fiber areas. This indicates that the sheet-like sandwich method makes it difficult for the phosphorus-containing binder phase to fully enter the core fiber network, resulting in insufficient bridging structure inside the core.
[0106] Figure 6 c and Figure 6 d. Further, the differences were magnified and observed using high-magnification SEM images. Figure 6 In Example c, a relatively continuous coating layer is visible on the fiber surface of Example 1, with fused bridges present at fiber intersections, and the pore edges remain clear. Combined with quantitative results, the cross-sectional SEM coating rate of Example 1 is 55.8%, and the proportion of fused bridges is 45.6%, indicating that its binder phase distribution has continuity and effective connectivity. Figure 6In example d, comparative example 10 shows an area rich in sheet-like binder phase or an area with insufficient bridging inside the core layer, indicating that its phosphorus-containing low-melting-point copolyester binder phase mainly stays in local layered areas and is difficult to form a relatively balanced connection structure in the fiber interwoven network.
[0107] Figure 6 e and Figure 6 The SEM-EDS surface scan results shown in f are used to compare the spatial distribution of P element signals within the field of view of the measured cross section. Figure 6 In e, the P element signal in Example 1 corresponds to the core fiber covering layer, the melt bridge, and the interlayer bonding region; Figure 6 In f, the P element signal in Comparative Example 10 is mainly concentrated in the lamellar interlayer or the upper molten film region, while the P signal inside the core layer is relatively less.
[0108] In conclusion, Figures 1 to 6 Table 1 illustrates the invention from aspects such as preheating conditions, thermal behavior, continuous process conditions, interface structure, and performance testing. By controlling the ratio of the porous PET fiber skeleton to the phosphorus-containing low-melting-point copolyester binder phase and the hot-pressing conditions, the low-melting-point phase forms a coating and molten bridge connection on the fiber surface and at fiber intersections. Simultaneously, the phosphorus element signal within the measured cross-sectional field of view is distributed along with the binder phase within the fiber network region. This structure retains the lightweight characteristics of the porous PET fiber core while improving interlayer bonding strength and the effective utilization rate of the phosphorus-containing structure, thereby addressing the technical challenge of simultaneously achieving low-density structure with flame retardant properties, processing fluidity, and heat resistance.
[0109] Table 1 Performance of Examples and Comparative Examples
[0110]
[0111] As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1–4 exhibit a more consistent level in terms of oxygen index, critical radiative flux, 180° peel strength, coverage, and melt bridge ratio. In the conventional comparative examples, deviations in the coefficients of variation of PET fiber content, phosphorus-containing low-melting-point copolyester binder phase content, hot-pressing temperature, hot-pressing pressure, and applied mass per unit area resulted in different directions of weakening of the lightweight structure, interlayer bonding, or dimensional stability. In the synergistic comparative examples, the absence of a low-melting-point copolyester binder phase containing 2-carboxyethylphenylphosphonic acid structural units, the application of sheet-like interlayers, and the omission of the preheating step all weakened the flame retardant contribution or the fiber cross-point connection tendency.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A lightweight PET fiber flame-retardant flooring, characterized in that, The PET is polyethylene terephthalate; the lightweight PET fiber flame-retardant flooring includes a PET surface layer, a PET fiber flame-retardant core layer, and a PET backing layer; Both the PET surface layer and the PET backing layer contain PET; The PET fiber flame-retardant core layer includes a PET fiber-phosphorus-containing low-melting-point copolyester coating, wherein the PET fiber-phosphorus-containing low-melting-point copolyester coating includes PET fibers and a phosphorus-containing low-melting-point copolyester binder phase coating the surface of the PET fibers and at the fiber intersections; Based on a 100wt% mass of the PET fiber flame-retardant core layer, the content of the PET fiber is 55–78wt%, the content of the phosphorus-containing low-melting-point copolyester binder phase is 18–40wt%, the sum of the contents of the PET fiber and the phosphorus-containing low-melting-point copolyester binder phase is 93–100wt%, and the balance is a PET transition phase located in the interface region of the PET fiber flame-retardant core layer. The apparent density of the PET fiber flame-retardant core layer is 0.55–0.95 g / cm³. 3 ; The phosphorus-containing low-melting-point copolyester binder phase is obtained by transesterification and polycondensation of dimethyl terephthalate, ethylene glycol, 1,4-cyclohexanediethanol and 2-carboxyethylphenylphosphonic acid in the presence of tetrabutyl titanate.
2. The lightweight PET fiber flame-retardant flooring according to claim 1, characterized in that, The PET fiber-phosphorus-containing low-melting-point copolyester coating is prepared through the following steps: A1. Providing a PET fiber felt, the PET fiber felt comprising PET fibers; A2. Provides a phosphorus-containing low-melting-point copolyester binder phase; A3. The PET fiber felt is compounded with the phosphorus-containing low-melting-point copolyester binder phase, such that the phosphorus-containing low-melting-point copolyester binder phase is distributed on the surface of the PET fiber and at the fiber intersections; A4. The composite material is preheated, hot-pressed, and cooled to set its shape; A5. After thickness determination and edge trimming, the PET fiber-phosphorus-containing low-melting-point copolyester coating is obtained; The moisture content of the PET fiber-phosphorus-containing low-melting-point copolyester coating is 0.02–0.30 wt%.
3. The lightweight PET fiber flame-retardant flooring according to claim 1, characterized in that, The phosphorus-containing low-melting-point copolyester binder phase is prepared through the following steps: B1. Raw material preparation: Based on 100 moles of dimethyl terephthalate, add 115–180 moles of ethylene glycol, 5–35 moles of 1,4-cyclohexanediol, 2–12 moles of 2-carboxyethylphenylphosphonic acid, and tetrabutyl titanate, wherein the amount of tetrabutyl titanate is 0.01–0.08 wt% of the total mass of dimethyl terephthalate, ethylene glycol, 1,4-cyclohexanediol, and 2-carboxyethylphenylphosphonic acid; B2. Transesterification reaction: The transesterification reaction is carried out under an inert atmosphere, and the methanol distillate is collected; B3. Polycondensation reaction: Polycondensation reaction is carried out under reduced pressure to obtain a molten phosphorus-containing low-melting-point copolyester; B4. Post-processing: The molten phosphorus-containing low-melting-point copolyester is extruded, cooled, pelletized, and dried to obtain the phosphorus-containing low-melting-point copolyester binder phase; The intrinsic viscosity of the phosphorus-containing low-melting-point copolyester binder phase is 0.45–0.80 dL / g, and the water content is 0.01–0.08 wt%.
4. The lightweight PET fiber flame-retardant flooring according to claim 1, characterized in that, The PET transition phase is a PET phase located in the interface region adjacent to the PET fiber flame-retardant core layer and the PET surface layer and / or the PET backing layer; the phosphorus-containing low-melting-point copolyester bonding phase forms a coating structure on the surface of the PET fiber and forms a melt bridge at the fiber intersection.
5. The lightweight PET fiber flame-retardant flooring according to claim 1, characterized in that, The thickness of the PET fiber flame-retardant core layer is 1.5–6.0 mm, and the recycled PET fiber in the PET fiber flame-retardant core layer accounts for 30–100 wt% of all PET fibers.
6. The lightweight PET fiber flame-retardant flooring according to claim 1, characterized in that, The lightweight PET fiber flame-retardant flooring has an oxygen index of 28–38 vol% as measured according to GB / T 2406.2-2009, and a critical radiant flux of 4.5–15.0 kW / m² as measured according to GB / T11785-2005. 2 .
7. The lightweight PET fiber flame-retardant flooring according to claim 1, characterized in that, The coefficient of variation for the thickness of the PET fiber flame-retardant core layer is 2–8%.
8. The lightweight PET fiber flame-retardant flooring according to claim 1, characterized in that, The melting peak temperature of the phosphorus-containing low-melting-point copolyester binder phase is 110–170℃; the phosphorus element in the PET fiber flame-retardant core layer is provided by the phosphorus-containing low-melting-point copolyester binder phase; no chlorine-based or bromine-based flame retardants are added to the PET fiber flame-retardant core layer; and the lightweight PET fiber flame-retardant floor does not include a polyvinyl chloride resin layer.
9. A method for preparing lightweight PET fiber flame-retardant flooring as described in any one of claims 1-8, characterized in that, The preparation method includes the following steps: S1. Provides a PET surface layer, a PET backing layer, and a pre-made PET fiber-phosphorus-containing low-melting-point copolyester coating; S2. The PET surface layer, the PET fiber-phosphorus-containing low-melting-point copolyester coating and the PET backing layer are stacked sequentially to obtain a laminate; S3. The laminate is hot-pressed and cooled to obtain the lightweight PET fiber flame-retardant flooring.
10. The preparation method according to claim 9, characterized in that, The cooling and shaping in step S3 includes cooling the laminate under pressure; the preparation of the PET fiber-phosphorus-containing low-melting-point copolyester coating and steps S2 and S3 are carried out sequentially using a continuous nonwoven web laying device, a continuous binder phase application device, and a continuous hot press roller pressing device; the total thickness of the obtained lightweight PET fiber flame-retardant flooring is 2.0–7.3 mm, and the interlayer 180° peel strength, calculated as the lower of the average peel strength of the stable peel zone at the interface between the PET surface layer and the PET fiber flame-retardant core layer and the interface between the PET fiber flame-retardant core layer and the PET backing layer, is 1.0–5.0 N / mm, with a thermal dimensional change rate of 0.02–0.30%.
Citation Information
Patent Citations
Flame-resistant polyester fiber and preparation method thereof
CN105463610A
